Knowledge and use of personal protective equipment by nursing professionals during the Covid-19 pandemic - Maria Sauanna Sany de Moura; Renata Kelly dos Santos e Silva; Priscila Martins Mendes; Antônia Sylca de Jesus Sousa; Francisco João de Carvalho Neto
ABSTRACT Objective: To explore the knowledge and use of personal protective equipment by nursing professionals of Primary Health Care during the Covid-19 pandemic. Method: This is an exploratory study of a non-probabilistic sample developed in Basic Health Units in the city of Picos, Piauí, Brazil. Data were collected between June and August 2020, by phone call, following a semi-structured script, with responses recording and transcription. For material analysis, the software IRaMuTeQ was used for statistical textual analyses: Descending Hierarchical Classification, similarity analysis, and word cloud. Results: From the corpus of 6,873 words and 832 lexical units, three categories were created: (1) motivations and barriers for use (20.9%); (2) handling of personal protective equipment (classes 5 and 4) with 25% and 21.6%, respectively, and (3) measures to protect users and health professionals (classes 3 and 5) with 17.6% and 14.9%. Conclusion: The nursing professionals interviewed demonstrated that they did not have sufficient knowledge for the proper use of the equipment, which could compromise their integrity and that of the patient as a subject who receives unsafe care.